Manajemen Pembelajaran Tahfiz Al- Qur’an dengan Metode UMMI di SDIT Abata Lombok - Firdaus, Andrian; Hadi, Alfan (Mataram University, 2024)
This study aims to know and analyze the implementation of the UMMI Method Tahfiz Al-Qur'an Learning Management at SDIT ABATA LOMBOK MATARAM, which includes basic aspects, planning, implementation, and supervision using qualitative research methods. In analyzing data, researchers use qualitative analysis techniques with the process of data reduction, data exposure and conclusions. The findings in this study are: First, the aspect that underlies the learning of the Qur'an tahfidz UMMI method is because the Qur'an learning method is holistic and comprehensive with the right brain under the auspices of Nur Amalia. Second, the UMMI method of planning Qur'anic tahfidz learning goes through a deliberation process that involves parties in the planning process. Third, the implementation of learning tahfidz Al-Qur'an ummi method in this study was carried out by dividing tahfidz groups based on the level of memorization. Fourth, Supervision of learning the Qur'an tahfidz ummi method carried out by the coordinator and central team, and supervised directly by the Principal by cross-checking again and providing guidance and direction for improvements to be made.